Integrating Cognitive Linguistics and foreign language teachingÂ· historical background and new developments - Rycker, Antoon De; Knop, Sabine De (Journal of Modern Languages, 2017)
Recently foreign language teaching (FLT) research has been able to benefit enormously from advances in Cognitive Linguistics (CL) (e.g. Lakoff, 1987; Langacker, 1991, Taylor, 2002). As a consequence, CL has become more and more interested in turning its rich, specialised, and emerging body of research into a practical guide for language teachers, course designers, and materials writers. To that end, CL-based classroom instruction in a second or foreign language needs to show that (i) it can move beyond the largely unmotivated rules, examples, and lists typical of the traditional paradigm; (ii) that it can produce results-driven grammar instruction and practice; and (iii) that it can ultimately balance all of this properly with new insights gained from second-language acquisition (SLA) research (e.g. Lantolf & Thorne, 2006). ln this paper, we will first look at CL in a broader historical context of applied linguistics, and more particularly, FLT, discussing how it builds on, and differs from, such linguistic theories as transformational-generative grammar and pragmatics. Then, we will show how the theoretical assumptions, basic units, and constructs used in CL offer a better understanding of the true nature of language and grammar, and how CL can improve the efficiency and effectiveness of current FLT methods (e.g. Robinson & Ellis, 2008; De Knop & De Rycker, 2008, Boers & Lindstromberg, 2008).